Translocation of chromosome 4 and 9 with ring formation of chromosome 4 short arm. Issue 4 (August 1978) - Bernstein, R; Milne, A T; Jenkins, T
Abstract : Cytogenetic investigation of a 3-year-old mentally retarded boy revealed a translocation of the long arm of chromosome 4 onto the short arm of chromosome 9, with ring formation of the remaining short arm of chromosome 4. The clinical features are described and correlated with the cytogenetic findings. The behaviour of the ring derived from a deleted chromosome 4 is discussed.